KARAKTERISASI TEPUNG BERAS TERFERMENTASI SECARA SPONTAN DAN TERKENDALI OLEH Lactobacillus casei - Nurhayati Nurhayati; Giyarto Giyarto; Dian Putri Ariyanti (Faculty of Agricultural Technology, University of Jember, 2014)
Rice flour contain starch more than 80% db. The digestibility of rice flour can increase by fermentation i.e fermentation of the lactic acid bacteria. The objective of this research was to characterize of the fermented rice flour using by Lactobacillus casei. The research was conducted with the fermentation of IR 64 rice variety using L. casei also by spontaneous fermentation during 24 and 48 hours. The result showed that the fermented rice flour using L. casei for 48 hours had the good characteristic were viscosity 27oC 1,38 Cp, viscosity 70oC 1,55 Cp, viscosity 90oC 5,63 Cp. The other characteristic of the best fermented flour were bacteria population 7,93 log CFU/ml, pH value 2,86, titrated lactic acid 1,20%, degree of whiteness 83,57, water content 8,69%, amylose content 27,95%db, amylopectin content 40,89%db, rate of digestable starch 37,09%db for rapid digestable starch (RDS), 24,97%db for slowly digestable starch (SDS), and 6,78% db resistant starch (RS), starch content 68,84%db, and digestibility value 90,07%db.Keywords: rice, flour, controlled and spontaneous fermentation, Lactobacillus casei